TINJAUAN KRITIS PERANAN PEMERINTAH DAERAH TERHADAP KINERJA ANGGARAN: PERSPEKTIF HUBUNGAN PRINCIPAL DAN AGENT - Cepi Pahlevi; Muhammad Idrus Taba; Muhammad Ismail; Mahlia Muis; Dian A.S. Parawansa; Siti Haerani; Haris Maupa; Sitti Rahmi Razak (ITB AAS Indonesia Surakarta, 2023)
This article presents a literature review relating to the role of local government on budget performance in three perspectives, namely: how the position and role of local governments towards budget performance, how the government's relationship with the Legislature and the Legislature's relationship with the public in the Principal and Agent Context, and how the Accountability Aspect in the Budgeting Perspective as a Political and Managerial Dimension. The method used is descriptive qualitative with a literature study approach. The results obtained show that, first, in the reform era, local government is seen as an entity that has broader authority. It has the authority to decide on the resources it uses. Second, the relationship between the legislature and the government assumes that the legislature will be the principal and the government the agent. The election process results in a mandate to the legislature to produce laws, oversee the work of the government and ensure all public policies will be implemented as stipulated. Third, In a democratic system, the role of the government, its objectives, policies, priorities and the specific programs it runs are fundamentally political and not managerial matters.